Enhancing Students’ Understanding Of English Grammar Through Literary Works And Exploring Students’ Voice On Their Use - Asfi Aniuranti; Dinar Faiza; Yasinta Wulandari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
Grammar is a substantial English element commonly considered as a challenging component. This paradigm appears in all education levels including university. Based on the pre-test in a grammar class, the average score of the grammar test was only 62.76, or it was still in C level. The researchers concurred that action research was required, and the solution chosen was literary works such as a short story, a film script, and a novel. This study aimed to enhance students' understanding of English grammar and investigate students' voices on the usage of literary works. This research was successful if the average score of post-test achieved 70 (minimum grade for B level). Then, the instruments employed to obtain the data were tests and questioner. The results revealed that literary works can boost grammar mastery. The average score of the post-test was 70.53, or there was a 12.38% of improvement. This result surpassed the success indicator of this action study. The student perceptions of the use of literary works also tended to be positive since all the items in the questioner received positive responses. Overall, literary works can enhance students' mastery of English structure, and literary works as the proposed media receive positive responses from the pupils.